Prey-predator phenological mismatch under climate change - Damien, Maxime; Tougeron, Kévin (Current opinion in insect science, 2019)
Insect phenology is affected by climate change and main responses are driven by phenotypic plasticity and evolutionary changes. Any modification in seasonal activity in one species can have consequences on interacting species, within and among trophic levels. In this overview, we focus on synchronisation mismatches that can occur between tightly interacting species such as hosts and parasitoids or preys and predators. Asynchronies happen because species from different trophic levels can have different response rates to climate change. We show that insect species alter their seasonal activities by modifying their life-cycle through change in voltinism or by altering their development rate. We expect strong bottom-up effects for phenology adjustments rather than top-down effects within food-webs. Extremely complex outcomes arise from such trophic mismatches, which make consequences at the community or ecosystem levels tricky to predict in a climate change context. We explore a set of potential consequences on population dynamics, conservation of species interactions, with a particular focus on the provision of ecosystem services by predators and parasitoids, such as biological pest control.
Keywords: predátorské chování; Insecta; klimatické změny; stadia vývoje; populační dynamika; Life Cycle Stages; Predatory Behavior; roční období; Animals; hmyz; Climate Change; Population Dynamics; zvířata; Biological Control Agents; Food Chain; Seasons; potravní řetězec; biologická ochrana